RELATIONSHIP BETWEEN SELF ESTEEM AND READING ABILITY OF INDONESIAN EFL STUDENTS - Intan Satriani (STKIP Siliwangi, 2017)
The present study is employed to understand the relationship between self esteemand reading ability of Indonesian EFL students. The study was conducted on bothIndonesian male and female graduate students of English department in aPostgraduate school in Bandung. During the research, questionnaire developed byHyde (1979 in Bagheri, et al., 2012) was used as the research instrument to obtainthe score of students‟ self esteem. In addition, the data of reading score werecollected from TOEFL score which has been standardized. Those instrumentswere administered in one session. The data were analyzed by Pearson momentcorrelation to identify the relationship between two variables. The result of thisstudy showed that the null hypothesis of this study is rejected. Sincetheprobability value of students‟ self esteem is lower than the level of significant(.697>0.05). It indicates that there is a correlation between self esteemandstudents‟ reading ability.Keywords: Self-Esteem , reading Ability